2020
DOI: 10.1002/brb3.1775
|View full text |Cite
|
Sign up to set email alerts
|

Subanesthetic dose of ketamine for the antidepressant effects and the associated cognitive impairments of electroconvulsive therapy in elderly patients—A randomized, double‐blind, controlled clinical study

Abstract: Objectives We previously confirmed that low‐dose ketamine, as an adjunctive anesthetic for electroconvulsive therapy (ECT) in adult patients with depression, accelerates the effects of ECT and reduces the ECT‐induced learning and memory deficits. This study explored the efficacy and safety of low‐dose ketamine in elderly patients with depression. Methods Elderly patients with depression (N = 157) were randomly divided into two groups: propofol anesthesia group (group P) and propofol combined with ketamine anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…Furthermore, the rational use of anesthetics such as propofol and ketamine can improve the e cacy of ECT [4][5][6] and may confer at least a short-term advantage in terms of improving depressive symptoms at the early stages of ECT 7 . A series of studies conducted by our research group also supported these views 8,9 .…”
Section: Introductionsupporting
confidence: 56%
“…Furthermore, the rational use of anesthetics such as propofol and ketamine can improve the e cacy of ECT [4][5][6] and may confer at least a short-term advantage in terms of improving depressive symptoms at the early stages of ECT 7 . A series of studies conducted by our research group also supported these views 8,9 .…”
Section: Introductionsupporting
confidence: 56%
“…Furthermore, the rational use of anesthetics, such as propofol and ketamine, can improve the efficacy of ECT [ 7 9 ] and may confer at least a short-term advantage in terms of improving depressive symptoms at the early stages of ECT [ 10 ]. A series of studies conducted by our research group also supported these views [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 57%
“…As shown in Figure 1 , from 856 records screened on title and abstract, 150 full texts were analyzed. The review process led to the selection of 22 studies (references reported in Table 1 ) referring to 22 independent RCTs (Loo et al, 2012 ; Zarate et al, 2012 ; Price et al, 2014 ; Rasmussen et al, 2014 ; Yoosefi et al, 2014 ; Alizadeh et al, 2015 ; Murrough et al, 2015 ; Singh et al, 2016 ; Zhong et al, 2016 ; Anderson et al, 2017 ; Fernie et al, 2017 ; Ray-Griffith et al, 2017 ; Chen et al, 2018 ; Taylor et al, 2018 ; Zhang et al, 2018 ; Dong et al, 2019 ; Fedgchin et al, 2019 ; Kheirabadi et al, 2019 ; Domany et al, 2020 ; Ochs-Ross et al, 2020 ; Keilp et al, 2021 ; Zou et al, 2021 ), 20 of these trials provided quantitative outcome data, therefore were included in the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%